We can never go back again, that much is certain. The past is still too close to us. / Δεν μπορούμε να ξαναγυρίσουμε πίσω - πάει, τελείωσε. Τα περασμένα είναι ακόμα πολύ κοντινά 2020-21 - Antoniou, Klitsa (My University, 2026)
We can never go back again, that much is certain. The past is still too close to us. / Δεν μπορούμε να ξαναγυρίσουμε πίσω - πάει, τελείωσε. Τα περασμένα είναι ακόμα πολύ κοντινά 2020-21 Exhibition Catalogue of an Art Intervention by the Fine Arts Department Cyprus University of Technology Exhibition, 2020 Organized and Curated by Klitsa Antoniou Catalogue Edited by Klitsa Antoniou ISBN-978-9963-697-41-0